Lipid Profiles In Serum Samples of Some Nigerian Male Subjects - EMMANUEL ILESANMI ADEYEYE; IDOWU OLUWADARE (International Journal of Pharma and Bio Sciences, 2011)
Excessive levels of cholesterol in blood circulation are strongly associated with progression of atherosclerosis. While the measurement of total cholesterol (TC) low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) are recommended in current cardiovascular screening algorithins, recent guidelines have emphasized the importance of non-high density lipoprotein cholesterol (non-HDL-C) as a predictor of cardiovascular risk, while others have strongly advocated the use of specific lipid ratios of TC to HDL cholesterol. This study examined clinical utility of atherogenic dyslipidemia, metabolic syndrome, non-HDL cholesterol and the lipid ratios (TC to HDL cholesterol, LDL to HDL cholesterol, TG to HDL cholesterol, non-HDL to HDL cholesterol) as an individual marker of cardiovascular events. Characterisation of the study subjects was given. The analyses of the biochemical parameters were done using Reflotron® System. The TC, HDL and TG (total glyceride) were measured directly. LDL-C was estimated using the Friedewald formula: [TC] – [total HDL-C] -20 % of the TG = estimated LDL-C based on the fact that TC is the sum of HDL, LDL and VLDL. The VLDL was estimated as one-fifth of TG. This formula was used to estimate LDL-C and VLDL-C in the samples. For the purpose of therapeutic decision-making, the followings were calculated: LDL-C/HDL-C, non-HDL-C/HDL-C, TG/HDL-C and TC/HDL-C ratios for the subjects. The results of the blood analyses revealed the total cholesterol (TC), total glyceride (TG) and the amounts of cholesterol in the various lipoproteins-high density lipoprotein-cholesterol (HDL-C), non-HDL-C, low density lipoprotein-cholesterol (LDL-C) and very low density lipoprotein-cholesterol (VLDL-C). 25 subjects were involved in the study. All TG levels < 200 mg/dl; all TC levels > 200 mg/dl; for HDL-C, 4 subjects (16 %) had values ≤ 35mg/dl; in LDL-C, all values > 130 mg/dl. For therapeutic decision – making, non- HDL-C/HDL-C, TC/HDL-C, TG/HDL-C and LDL-C/HDL-C were calculated. In TC/HDL-C, only one subject (4 %) had value of ≤ 3.4 and in LDL-C/HDL-C, 22 subjects (88 %) had values < 5.0. Hence, non-HDL,TC, HDL-C, LDL-C, TC/HDL-C and to a lesser extent LDL-C/HDL-C could contribute to increased atherosclerotic heart disease such as hypercholesterolemia and/or low HDL cholesterolemia in the subjects. All the results were matched for age and sex. This report showed that significantly different results existed in TC and HDL-C (group II); VLDL-C and TG (group III) and LDL-C/HDL-C (group III); TG/HDL-C (group IV). All TG levels were < 200 mg/dl, all TC levels > 200 mg/dl; all levels in LDL-C were > 130 mg/dl and in LDL-C/HDL-C 88 % subjects had values < 5.0. Hence, TC, HDL-C, LDL-C, TC/HDL-C and to lesser extend LDL-C/HDL-C could contribute to increased risk of atherosclerotic heart disease and familial hyperlipoproteinemia.